Properties of a CCAAT box-binding protein. - Hooft van Huijsduijnen, R A (1987)
NF-Y is a sequence-specific DNA-binding protein that interacts with the conserved Y motif of the major histocompatibility complex class II gene, E alpha. Since it is actually a CCAAT box-binding protein, NF-Y also attaches to other promoters bearing CCAAT sequences; yet, it is neither of the previously described transcription factors, CBP or CTF/NF-1. In this report, we document the cell-type distribution and various biochemical properties of NF-Y. The most important findings are that this protein is ubiquitously distributed, that it is probably a metallo-protein, that it has a protease-resistant DNA-binding domain and that the NF-Y/E alpha-olgo complex seems extremely large (greater than 200kD). These data should prove useful in comparisons of NF-Y with other sequence-specific DNA-binding proteins; they have already provided new insights into NF-Y's structure.